Free nitrous acid inhibition on carbon storage microorganisms: Accumulated inhibitory effects and recoverability - Ganda, Lily (2016)
Recent research has shed light on utilization of carbon storage microorganisms in the A-stage of AB process for higher methane generation and resource recovery potential. Typically, organic matters are entrapped into biomass in the A-stage and subsequently channeled to the anaerobic digester for energy/resource recovery. In the following B-stage, nitrite shortcut strategy is often implemented to achieve low energy nitrogen removal. In this study, an enriched glycogen accumulating organism (GAO) culture was deployed as the A-stage carbon storage microorganisms to enhance the removal of soluble COD. This study aimed (1) to address the challenge arising from incidental nitrite leakage into the A-stage tank, leading to free nitrous acid (FNA) inhibition; and (2) to evaluate the continued (henceforth referred to as ‘accumulated’) inhibitory effects on GAOs’ carbon metabolisms under the subsequent FNA-free condition. Upon FNA exposure, dynamics in carbon storage mechanisms were obtained and could be linked to higher cellular energy expenditure for detoxification activity. The inhibition on carbon transformation, however, was found to be reversible, suggesting the robustness of GAO towards FNA inhibition and its potential application in the nitrite-shortcut AB process.